THE INFLUENCE OF PSYCHOLOGICAL WELFARE AND LEADER-MEMBER EXCHANGE ON WORK ENGAGEMENT FOR CLASS I MEDAN BAPAS PNS - Ika Rasidina Daya; Rahmi Lubis; Yudistira Fauzy Indrawan (RADJA PUBLIKA, 2024)
This study aims to determine the effect of psychological well-being and leader-member exchange on work engagement in the Civil Servants of Bapas Class I Medan. The population in this study were 140 civil servants. Sampling in this study uses a total sampling technique, where the entire population is the sample. This study uses quantitative methods using psychological well-being, leader-member exchange (LMX) and work engagement variables. The data analysis technique used in this study is multiple regression analysis. The results indicated that (1) There is a significant positive effect of psychological well-being on work engagement where 20.2% of the work engagement variable can be explained by the psychological well-being variables. (2) There is a significant positive effect of leader-member exchange on work engagement where 13.1% of the work engagement variable can be explained by the leader-member exchange variable. (3) There is a significant positive effect of psychological well-being and leader-member exchange on work engagement, where 22.7% of the work engagement variable can be explained by the independent variable, namely psychological well-being and leader-member exchange, while 77.3% is explained by other variables not explained in this study.